Determinação experimental da carga de flambagem e da excentricidade acidental de pilares compostos de madeira - Flavia Caetano Carvalhar (2001)
This work involves the experimental study of the buckling of composed section timber columns. The objective is to compare the experimental results with the analytical results established by the Brazilian Norm. Five columns of composed sections were tested and it was conducted through two timber parts nailed by five spacers equally distributed along the columns. Then, it was made a comparison between the obtained results in the experimental tests and the results described in the Brazilian Norm (NBR 7190/1997).